FimH confers mannose-targeting ability to Bacillus Calmette-Guerin for improved immunotherapy in bladder cancer - Yang Zhang; Chao Yan; Ru Jia; Qiang Lv; Fan Huo; Qiang Cao; Qiju Huang; Zhu A Wang; Dan Theodorescu; Pengchao Li (Journal for ImmunoTherapy of Cancer)
Background Bladder cancer is a common disease worldwide with most patients presenting with the non-muscle-invasive form (NMIBC) at initial diagnosis. Postoperational intravesical instillation of BCG is carried out for patients with high-risk disease to reduce tumor recurrence and progression to muscle invasive disease. However, BCG can also have side effects or be ineffective in some patients because it cannot enter the cancer cells. Thus, to improve the efficacy of BCG immunotherapy is the long-term pursuit of the bladder cancer field.Methods To increase the adhesion of BCG to the urothelium we overexpressed FimH, a mannose binding protein naturally used by uropathogenic Escherichia coli to adhere to human urothelium, onto the surface of BCG. The adhesion/internalization ability of rBCG-S.FimH was examined in mouse bladder by fluorescence microscopy. Preclinical evaluation of antitumor efficacy was carried out in orthotopic mouse models of bladder cancer and in human peripheral blood mononuclear cells. Mechanistic studies were carried out using toll-like receptor 4 (TLR4) knockout mice. Immune cells and cytokines in the serum, tumor and lymph nodes were analyzed by flow cytometry, PCR, ELISA and ELISPOT.Results rBCG-S.FimH exhibited markedly improved adhesion and more rapid internalization into urothelial cells than wild-type BCG, resulting in more potent antitumor activity in orthotopic murine models of bladder cancer. To our surprise, rBCG-S.FimH elicited a much more prominent Th1-biased immune response known to be positively correlated with BCG efficacy. Mechanistic studies using TLR4 knockout mouse showed that rBCG-S.FimH could induce enhanced dendritic cell activation and tumor antigen-specific immune response in a TLR4-dependent manner. Furthermore, human peripheral blood mononuclear cells stimulated by rBCG-S.FimH also showed better tumoricidal effects than those using wild-type BCG.Conclusion rBCG-S.FimH is a novel BCG strain with significantly improved efficacy against bladder cancer. Since intravesical BCG immunotherapy is the first-line treatment for NMIBC, which accounts for more than 70% of all bladder cancer cases, our results provide a compelling rationale for clinical development.